Планирование потребности в материальных ресурсах на предприятии - Баскин Аркадий Исаакович (Технiка, 1983)
Экземпляры: КХ (20120727) / Инвентарный номер: 0262595 / Цена: 0.20 / Сис.шифр: 6 / Авт.знак: Б 27 / ГРНТИ: 81 / ББК: 3